1983
DOI: 10.1080/14640748308402136
|View full text |Cite
|
Sign up to set email alerts
|

Visual Control of Discrete Aiming Movements

Abstract: An experiment is reported which investigated the visual control of discrete rapid arm movements. Subjects were required to move as rapidly as possible to several target width-movement distance combinations under both visual and non-visual conditions. The movement time (MT) data were supportive of Fitts' Law in that MT was linearly related and highly correlated to the Index of Difficulty (ID). MT was also similar for different target width-distance combinations sharing the same ID value. The error rate analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
53
0
2

Year Published

1989
1989
2015
2015

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(61 citation statements)
references
References 19 publications
6
53
0
2
Order By: Relevance
“…In the more affected arm, both increased skewness (conservative planning strategy) and segmentation (trajectory corrections) were related to the intercept, while reduced directness (path accuracy and execution) was related to increased transmission capacity (i.e., slope −1 ). Wallace and Newell (1983) found that in healthy subjects, there is an increased reliance on sensory feedback for increasing accuracy requirement suggesting that there is a gradual shift from a feedforward to a feedback model of control depending upon the difficulty of the task (Siegel, 1977). The steeper slope in the Fitts' relation, together with the increased skewness and segmentation of profiles for the more affected arm of subjects with stroke, suggests that this shift from feedforward to feedback loop control occurs at reduced levels of accuracy for movement of the more affected arm.…”
Section: Consequences Of Increased Neuromotor Noise On Trajectory Formentioning
confidence: 99%
“…In the more affected arm, both increased skewness (conservative planning strategy) and segmentation (trajectory corrections) were related to the intercept, while reduced directness (path accuracy and execution) was related to increased transmission capacity (i.e., slope −1 ). Wallace and Newell (1983) found that in healthy subjects, there is an increased reliance on sensory feedback for increasing accuracy requirement suggesting that there is a gradual shift from a feedforward to a feedback model of control depending upon the difficulty of the task (Siegel, 1977). The steeper slope in the Fitts' relation, together with the increased skewness and segmentation of profiles for the more affected arm of subjects with stroke, suggests that this shift from feedforward to feedback loop control occurs at reduced levels of accuracy for movement of the more affected arm.…”
Section: Consequences Of Increased Neuromotor Noise On Trajectory Formentioning
confidence: 99%
“…Three target amplitudes were employed in an attempt to reduce the predictability of the specifics of an upcoming trial and, thus, in turn to reduce the degree to which movements could be influenced by offline processing. The task itself-namely a simple discrete reaching movement-was chosen to provide a straightforward context from which to infer changes in performance due to online feedback utilization, while also being consistent with the literature that has investigated online control mechanisms (e.g., Plamondon & Alimi, 1997;Wallace & Newell, 1983).…”
Section: Methodsmentioning
confidence: 90%
“…Such an effect can theoretically be attributed in part to the temporal costs associated with the use of feedback (see Fitts, 1954). Indeed, when utilizing targets with relatively high indices of difficulty (i.e., indices of difficulty above 3.58 bits; see Wallace & Newell, 1983), FV-versus-NV performance differences may be more confidently associated with visual feedback utilization. As such, in the present study we employed targets approximately 1 cm in width at distances ranging from 27 to 33 cm, yielding indices of difficulty from 5.75 to 6.04 bits.…”
Section: Conventional Measures Of Online Feedback Utilizationmentioning
confidence: 99%
“…However, Wallace and Newell (1983) condition, resulting in initial saturation of most cone and some rod photopigments. As these photopigments regenerate, sensitivity to light progressively improves.…”
Section: Sterbers Additive Factors Modelmentioning
confidence: 99%
“…Distorting the perception of the stimuli is an alternative approach to altering the stimuli directly (illuminated vs. dark conditions). One method to test Wallace and Newell's (1983) hypothesis is to use participants who are partially sighted. This could provide evidence that as the ID increases the need for vision increases.…”
Section: Sterbers Additive Factors Modelmentioning
confidence: 99%